A Fruitful Field: Recent Study of the Acts of the Apostles - Gasque, W. Ward (Interpretation, 1988)
One conclusion that unites nearly all recent study of Luke-Acts is that Conzelmann's classic formulation of the purpose of the Lukan writings, put forward in The Theology of St. Luke, was incorrect.